SLOPE STABILITY ANALYSIS OF AMERORO DAM - Rahmat Hidayat; Amrinsyah Nasution; Hanafi Ashad (Jurnal Scientia, 2023)
The Ameroro Dam was built by the Sulawesi IV River Basin Center (BWS), Directorate General of Water Resources of the Ministry of PUPR with a storage capacity of 44.44 million m3 in order to increase the Irrigation Area (DI) in Konawe Regency. The Ameroro Dam is designed with the urugan type which has a peak height of 82 meters, a dam length of 324 meters, and a width of 12 meters. The spillway building has a threshold elevation of 122.50 meters with the Ogee type, a dodger channel in the form of double concrete conduits, and a Submerged Intake Tower retrieval building type. This study aims to analyze the slope stability of the Ameroro dam. This research studies slope stability using several methods; (a) Spencer Method (b) Finite Element Method. This research takes a research case study in Ameroro Dam, Konawe Regency, Southeast Sulawesi Province, Indonesia. The primary data from this study is in the form of documentation of conditions in the field. The results of this study state that from the results of the slope stability analysis, it was found that the safety factor on the slopes contained in the Ameroro Dam was 1.79. Slope conditions are relatively stable. And from the results of the comparison of slope stability analysis with the spencer method and finite element method, the safety factor value of the spencer method was 1.347, while the safety factor value of the finite element method with PLAXIS 2D software analysis was 1.67. So the lower bound SoF value = 1.347 from the spencer method calculation and the upper bound SoF value = 1.67 from the PLAXIS 2D software analysis calculation